2021
DOI: 10.1007/s11187-021-00474-9
|View full text |Cite
|
Sign up to set email alerts
|

SMEs’ line of credit under the COVID-19: evidence from China

Abstract: How does the COVID-19 affect SMEs’ financing in emerging markets? In this paper, we investigate the impact of the COVID-induced shock on Chinese SMEs’ line of credit (LOC) using deal-level data. As Hubei province was mostly affected, we employ a difference-in-differences approach with the propensity score matching (PSM-DID) and compare Hubei SMEs’ credit responses before and after the outbreak relative to those of non-Hubei SMEs. Our results suggest that Hubei SMEs’ credit demand reduced significantly compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“… Fairlie and Fossen (2022a) provide a disbursement analysis of the Paycheck Protection Program and the Economic Injury Disaster Loan Program, both in the US, that aimed to help disadvantaged groups. For China, Liu, Zhang, Fang, and Chen (2022) show the supportive role of Chinese state-owned banks for small businesses’ lines of credit, where the broad policy mix comprised loan guarantees, direct lending to SMEs, grants, and equity instruments. Belghitar, Moro, and Radić (2022) investigate the effects of UK governmental policies for SMEs during Covid-19 and examined their effect on the ability to survive the pandemic.…”
Section: Covid-19 and Self-employmentmentioning
confidence: 99%
“… Fairlie and Fossen (2022a) provide a disbursement analysis of the Paycheck Protection Program and the Economic Injury Disaster Loan Program, both in the US, that aimed to help disadvantaged groups. For China, Liu, Zhang, Fang, and Chen (2022) show the supportive role of Chinese state-owned banks for small businesses’ lines of credit, where the broad policy mix comprised loan guarantees, direct lending to SMEs, grants, and equity instruments. Belghitar, Moro, and Radić (2022) investigate the effects of UK governmental policies for SMEs during Covid-19 and examined their effect on the ability to survive the pandemic.…”
Section: Covid-19 and Self-employmentmentioning
confidence: 99%
“…Different interventions by governments have led to soften some consequences in order to sustain a minimum of economic activity, although the growth in public deficit that results will limit such actions in the future, while more pandemics are to come. Also, banking institutions are less inclined to support SMEs in periods of crises, as many authors have noticed, including Liu et al (2021) among Chinese companies and Calabrese et al (2020) among SMEs from the United Kingdom. Block et al (2021) have shown the advantages of BF practices among young and very small companies in times of crises, while our results, observed on healthy companies that are older and more mature, beckon to consider other business practices that can impact liquidities.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be indispensable to allow SMEs to go through periods of major crises, such as the COVID-19 sanitary crisis. Indeed, in such a context, financial institutions face heavy constraints that render them overcautious about financing risky activities that are connected to the growth of SMEs and for which future benefits are uncertain (Calabrese et al, 2020;Liu et al, 2021). Likewise, public authorities, having supported those companies in times of crises and exacerbated their budget deficits, are unable to sustain their roles of coordination and support to SMEs (Belghitar et al, 2021;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, private firms are restricted from leveraging resources. Meanwhile, state-owned firms, even though their access to key strategic resources is unhindered, may fail to utilise these resources effectively to maximise profits due to agency problems associated with the manager-owner governance system (Liu, Zhang, Fang, & Chen, 2021), which prevent them from operating an efficient system of corporate governance. In this regard, the establishment of mixed ownership hybrid firms, in accordance with resource dependence theory (RDT) (Pfeffer & Salancik, 1978), may be a solution.…”
Section: Hybrid Firms Private Firms and State-owned Firmsmentioning
confidence: 99%
“…These competitive advantages come from (1) access to key strategic resources, and (2) improved legitimacy. Meanwhile, hybrid firms may be more efficient than state-owned firms in utilising resources because they face fewer owner-manager agency problems (Liu et al, 2021). As such, we draw upon the RDT and legitimacy viewpoint to highlight the importance of hybrid firms' capacity to gain access to external resources and establish their legitimacy, leading to improved performance ultimately.…”
Section: Hybrid Firms Private Firms and State-owned Firmsmentioning
confidence: 99%